Adolescent childbirth in the service area of Walelagama Primary Health Center, Jayawijaya Regency: A phenomenological study - Nuriati Sarlota Auparai; Rosmin Mariati Tingginehe; Arius Togodly (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Early-age childbirth remains an important reproductive health problem because it increases maternal, neonatal, psychosocial, educational, and social risks, particularly in geographically isolated communities. Purpose: To explore women’s lived experiences, family and community perceptions, socio-cultural conditions, educational and socioeconomic contexts, and access to reproductive health information and services related to early-age childbirth. Method: A qualitative phenomenological design was used. Informants were selected purposively and consisted of women who gave birth before the age of 20 years, husbands or family members, health workers, and community figures. Data were collected through in-depth interviews supported by field notes and were analyzed thematically using data reduction, data display, and conclusion drawing. Results: Five themes emerged: difficult childbirth experiences, normalization of early-age childbirth, shifting socio-cultural influences, limited education and economic readiness, and restricted access to reproductive health information and maternal health services. Conclusion: Early-age childbirth in this setting is shaped by interconnected individual, family, socio-cultural, economic, and health-service factors. Community-based reproductive health education, stronger family involvement, and culturally sensitive adolescent-friendly maternal health services are needed to reduce early-age childbirth.